(untitled) (Journal of Face Aesthetics, 2024)
Granuloma Faciale is a rare and chronic skin disease. Although many therapeutic options have been described, general and topical treatment often does not bring satisfactory results and invasive modalities may result in scarring or hyperpigmentation. We report a case of Granuloma faciale in a 50-year‑old man. He reported to our clinic with reddish papules on the forehead. Histopathological examination confirmed a diagnosis. The treatment included clobetasol propionate followed by tacrolimus with no improvement. The patient was then given intralesional triamcinolone (0.01 g/ml in doses of 0.6ml). Four procedures with 6-weeks intervals were performed. A complete resolution of the lesion with no adverse effects was observed. Although the lesions are difficult to treat with a tendency to recur, they can be successfully treated with intralesional triamcinolone with perfect aesthetic outcome. Such treatment shall be considered a first‑line therapy due to highly satisfying cosmetic results, cost‑effectiveness and minimal risk of adverse effects.